Analisis Yuridis Penegakan Hukum Terhadap Pelaku Penyalahgunaan Narkoba Untuk Menimbulkan Efek Jera Dengan Sanksi Pidana - Uyat Ruhyat; Ardiansyah Ardiansyah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Countless drug eradication efforts have been carried out by the government, but it is still difficult to prevent these narcotics from entering people's lives. By declaring 2014 as the year to save drug users, drug addicts must be handled properly, not only subject to imprisonment but also other measures such as rehabilitation which are permitted by law to provide a deterrent effect for the perpetrators or abusers. The formulation of the problem discussed is: 1) How are criminal sanctions applied to drug abusers to provide a deterrent effect? 2) What are legal consideration for drugs abuser in determining criminal Sanction.? The research method used is the normative juridical method, namely research that prioritizes library data, namely research on secondary data. Secondary data can be in the form of primary, secondary or tertiary legal materials. This research includes research regarding positive legal provisions that apply in Indonesia. Based on the research results, the author concludes that legal considerations in determining rehabilitation for victims of narcotics abuse are in accordance with the provisions of Article 127 paragraph (3) which states that if a Class I narcotics abuser is proven to be a victim of narcotics abuse, the abuser is obliged to undergo medical rehabilitation and social rehabilitation. In determining that an abuser must undergo rehabilitation, there must be evidence that proves that the abuser is a victim and this evidence can be obtained through an assessment from the hospital and/or rehabilitation center as well as information from an expert, namely a doctor who provides information on the extent of his or her dependency and the existence of an application. rehabilitation on the part of the defendant.